Creep behavior of EPS composite soil - Gao, HongMei (2013)
EPS composite soil is one type of premixed lightweight fills studied by numerous researchers. However, one aspect that has not been fully understood is the creep behaviors which may have significant effect on the design and application of EPS composite soil. In this paper, the results of a series of oedometer creep tests and triaxial undrained creep tests on EPS composite soil were presented. Four main influencing factors were identified and their effects on the creep behaviors of EPS composite soil were studied. Three well established creep models, namely, Findley model, Singh & Mitchell model, and Mesri model, were used to simulate the creep behavior of EPS composite soil. This study shows that the Findley creep model fits the test results the best. A semi-empirical creep model was also proposed to model the creep behavior under axisymmetric conditions. In this model, the creep strain was divided into instant and viscous elastic strain as well as instant and viscous plastic strain which were simulated by element models and empirical equations, respectively. It was shown that the proposed creep model was able to precisely predict the creep strain of EPS composite soil.